A Novel Three-Level Soft-Switching Inverter Based on Auxiliary Resonant Pole - Zhou, Yan; Lehmeier, Thomas; März, Martin; Pai, Ajay Poonjal (2025 Energy Conversion Congress & Expo Europe (ECCE Europe), 2025)
Soft-switching in power converters offers a highly attractive solution for enhancing system efficiency by minimizing switching losses and mitigating electromagnetic interference. This article introduces a novel three-level soft-switching inverter topology based on the Auxiliary Resonant Pole (ARP), which modifies the well-known Auxiliary Resonant Commutated Pole (ARCP). The proposed topology is derived from the hard-switched Active Neutral Point Clamped (ANPC) inverter structure and is divided into a high-frequency stage and a low-frequency stage. By integrating an ARP cell into an ANPC, the new design retains the benefits of conventional three-level inverters, such as lower voltage stress on components and high-quality output waveforms, while simplifying the control complexity typically associated with ARCP. A 10 kW prototype with a 1.5 kV dc-link, along with an appropriate control algorithm, was implemented to experimentally validate the concept. The measurement results confirm the functionality of the proposed solution, achieving a peak efficiency of 99.4% without introducing significant drawback
Keywords: Semiconductor device measurement; Silicon carbide; Switching loss; Europe; Zero voltage switching; Inverters; Topology; Zero current switching; Stress; Standards

Efficiency Investigation of Full-SiC versus Si-based Automotive Inverter Power Modules at Equal Commutation Speed - März, Martin; Pai, Ajay Poonjal; Reiter, Tomas (2018 PCIM Europe, 2018)
This paper investigates the mission profile efficiency performance of a full-SiC power module based on Infineon’s Automotive CoolSiCTM MOSFET technology, suitable for traction inverter applications. This module is compared against a full-Silicon (Si) and a hybrid Silicon Carbide (SiC) module. The comparison is performed in identical state-of-the-art automotive power module package with 8 nH stray inductance (HybridPACK Drive). A commutation-speed based methodology is introduced to ensure that all devices are switching at the same speed for comparison. Static and dynamic characterisation of the three modules are performed, and these measurements are used to perform power loss calculations for different mission profiles and the full-SiC module was found to offer over 60% reduction in the total losses compared to the full-Si module.<br
Keywords: Efficiency investigation; Si-based; Equal commutation speed

Influence of SiC MOSFET Device Parameters on Zero-Voltage Switching Losses - Lehmeier, Thomas; Zhou, Yan; März, Martin; Pai, Ajay Poonjal (PCIM Conference 2025; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2025)
Soft-switching in power converters offers a highly attractive solution to enhance system efficiency by reducing switching losses while also mitigating electromagnetic interference. Although zero-voltage switching (ZVS) significantly reduces switching losses, it does not eliminate them. Considerable turn-OFF losses remain, dependent on transistor parameters such as internal gate resistance, threshold voltage, and parasitic device capacitances. To analyze the influence of these parameters, 1200V SiC MOSFETs from different manufacturers and latest-generation technologies are examined. The residual ZVS losses are measured using a calorimetric method within a half-bridge circuit operated under ZVS up to 350 kHz at an 800V dc-link. This article assists designers in selecting the most suitable power semiconductor devices for soft-switched converters operating at frequencies of up to several hundred kilohert
CRIS-Team Scopus Importer:2025-08-29